1994
DOI: 10.1111/j.1472-765x.1994.tb00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNAse activity in PFGE analysis of DNA from Campylobacter jejuni

Abstract: DNAse-positive strains of Campylobacter jejuni degrade their chromosomal DNA during standard preparative procedures before pulsed-field gel electrophoresis (PFGE). A simple method for inactivation of this DNAse activity is described. Formaldehyde fixation of the bacterial cells resulted in the preservation of the DNA in a state suitable for restriction digestion and subsequent electrophoretic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 7 publications
0
76
0
2
Order By: Relevance
“…The preparation of bacterial DNA for PFGE and the separation of Srma I restriction fragments using a CHEF-DR II system (Bio Rad Laboratories, USA) were as previously described [10]. In brief, the bacterial cells were incorporated into 1 % w/v agarose plugs and lysed for 48 h at 56 'C in two changes of solution containing 1 % w/v N-Lauroyl sarcosine, 0 5 mM-EDTA pH 9 5 and 0-5 mg/ml proteinase K. The plugs were washed and stored at 4 'C in Tris-EDTA buffer (10 mm-Tris, 10 mm-EDTA, pH 7 5).…”
Section: Pulsed Field Gel Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of bacterial DNA for PFGE and the separation of Srma I restriction fragments using a CHEF-DR II system (Bio Rad Laboratories, USA) were as previously described [10]. In brief, the bacterial cells were incorporated into 1 % w/v agarose plugs and lysed for 48 h at 56 'C in two changes of solution containing 1 % w/v N-Lauroyl sarcosine, 0 5 mM-EDTA pH 9 5 and 0-5 mg/ml proteinase K. The plugs were washed and stored at 4 'C in Tris-EDTA buffer (10 mm-Tris, 10 mm-EDTA, pH 7 5).…”
Section: Pulsed Field Gel Electrophoresismentioning
confidence: 99%
“…The blocks were loaded onto a 1 % w/v agarose gel prepared in 0 5 x TBE (45 mM-Tris, 45 mm boric acid, 1 mM-EDTA). Electrophoretic separation of Sma I generated fragments was at 200 V, 14 C, for 22 h with ramped pulse times from 10 to 35 s; of Kpn I generated fragments, 200 V, 14°C, 23 h with ramped pulse times from 4 to 20 s. DNA degradation in Lior biotype II (DNase positive) strains was prevented by formaldehyde fixation of the bacterial cells prior to their incorporation into agarose [10].…”
Section: Pulsed Field Gel Electrophoresismentioning
confidence: 99%
“…jejuni isolates were grown on sheep blood 5% agar for 48 h at 378C in a micro-aerobic atmosphere. Bacterial colonies were harvested, resuspended in 900 ìl of cold saline and treated with 100 ìl of formaldehyde on ice for 1 h to inactivate endogenous nucleases [12]; bacterial suspensions were then washed three times in 1000 ìl of cold saline by centrifugation at 12 000 rpm and resuspended in 1000 ìl of saline. The optical densities of the bacterial suspensions were then adjusted to 1.9 at 405 nm and 625-ìl samples were gently mixed with 375 ìl of InCert agarose 1.5% (FMC BioProducts, Rockland, ME, USA).…”
Section: Pfgementioning
confidence: 99%
“…Thus, PFGE typing might be suitable for epidemiological investigations of the P. pneumotropica isolates. extensive degradation of the genomic DNA (2,12,16,22,26). Evans et al (11) reported that DNA degradation was caused by free radicals in tris buffer during the electrophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…Although we tried a method which prevents DNA degradation by adding a free radical scavenger such as thiourea to the PFGE buffer (18), the DNA banding patterns were not obtained in this study. We further examined the formaldehyde fixation method (12), and heat treatment (22,24). However, the DNA banding patterns were not obtained.…”
Section: Discussionmentioning
confidence: 99%